Pengembangan formula enteral hepatogomax untuk penyakit hati berbasis tepung kedelai dan tepung susu kambing - Rahmadanti, Tia Sofa; Candra, Aryu; Nissa, Choirun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Patients with chronic liver disease were risk to be malnourished due to malabsorption, hipermetabolic condition, and not receiving adequate nutrients orally. Diet therapy through enteral feeding based on soybean flour and goat milk flour play role as an alternative formula for chronic liver patients since it contains high Branched-Chain Amino Acids (BCAA) and Medium-chain Triglyceride (MCT).Objectives: to analyze viscosity, nutrient content, protein digestibility, and organoleptic properties of enteral feeding using soybean flour and goat milk flour.Methods: An experimental study using 3 distinc formula with ratio soybean flour to goat milk flour was P1(45:55), P2(50:50), P3(55: 45).  Viscosity, fat, carbohydrate content, and energy density were analyzed using One Way Anova followed by Tukey test while protein content, protein digestibility, and energy density were analyzed using Kruskal Wallis followed by Mann Whitney test. Organoleptic properties were analyzed using Friedman followed by Wilcoxon test.Results:The higher the soybean flour, the higher the formula viscosity (p=0.000) and protein (0.007). In contrast, the higher the got milk flour, the higher the fat (p=0.000), carbohydrate (p=0.000), energy (p=0.000) and energy density (p=0.013). Formula P3 has the highest viscosity (1.93±0.039 cP) and protein (9.66±0.16%), while P1 has the highest fat (27.33±0.15%), carbohydrate (65.97±0.23%), energy (1.175±3.04 kkal), energy density (1.17±0.00 kkal/ml), and protein digestibility (45.90±1.49%) among others. However, there is no effect of different formula toward protein digestibility (p=0.116). Organoleptic properties showed that the higher the got milk flour, the higher its acceptance in all aspect including color (p=0.046), flavor (p=0.000), taste (p=0.009) dan texture (p=0.002).Conclusion: P1 was the best formula due to its level of viscosity, fat, energy, protein and energy density that meet requirements according to European Society for Clinical Nutrition and Metabolism (ESPEN). P1 also has the highest protein digestibility, and have the highest score of all organoleptic parameters.